Transporter-Targeted Lipid Prodrugs of Cyclic Cidofovir: A Potential Approach for the Treatment of Cytomegalovirus Retinitis - Gokulgandhi, Mitan R. (J Pharm Sci, 2012)
Cidofovir (CDF) and its cyclic analogue (cCDF) have shown potential in vitro and in vivo antiviral activity against cytomegalovirus (CMV) retinitis. However, hydrophilic nature of CDF may affect cell permeation across lipophilic epithelium and thus limit its effectiveness in the treatment of CMV retinitis. In the present study, we have tested a novel hypothesis, which involves chemical derivatization of cCDF into lipophilic transporter-targeted prodrug [via conjugation with different carbon chain length of lipid raft and targeting moiety (biotin) for sodium-dependent multivitamin transporter (SMVT)]. We have synthesized and characterized three derivatives of cCDF including biotin B-C2–cCDF, B-C6–cCDF, and B-C12–cCDF. Physicochemical properties such as solubility, partition coefficient (n-octanol/water and ocular tissue), bioreversion kinetics, and interaction with SMVT transporter have been determined. Among these novel conjugates, B-C12–cCDF has shown higher interaction to SMVT transporter with lowest half maximal inhibitory concentration value, higher cellular accumulation, and high tissue partitioning. Improvement in physicochemical properties, lipophilicity, and interaction with transporter was observed in the trend of increasing the lipid chain length, that is, B-C12–cCDF > B-C6–cCDF > B-C2–cCDF. These results indicate that transporter-targeted lipid analogue of cCDF exhibits improved cellular accumulation along with higher transporter affinity and hence could be a viable strategy for the treatment of CMV retinitis.